Accumulation of geometrically necessary dislocations near grain boundaries in deformed copper - Jiang, J; Britton, T; Wilkinson, A (2012)
Cross-correlation-based analysis of electron backscatter diffraction patterns has been used to map the distribution of geometrically necessary dislocation (GND) density in deformed polycrystalline copper. Patterning of the dislocations into high-density cell walls and low-density cell interiors was readily observed at the micron scale. Patterning at the longer length scale of the grain size was also evident with high-density regions (GND hot spots) tending to be in clusters, often found close to some but not all grain boundaries and triple junctions. © 2012 Copyright Taylor and Francis Group, LLC.